2016
DOI: 10.1186/s12968-017-0359-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of myocardium at risk in ST- elevation myocardial infarction: a comparison of contrast-enhanced steady-state free precession cine cardiovascular magnetic resonance with coronary angiographic jeopardy scores

Abstract: BackgroundClinical outcome following acute myocardial infarction is predicted by final infarct size evaluated in relation to left ventricular myocardium at risk (MaR). Contrast-enhanced steady-state free precession (CE-SSFP) cardiovascular magnetic resonance imaging (CMR) is not widely used for assessing MaR. Evidence of its utility compared to traditional assessment methods and as a surrogate for clinical outcome is needed.MethodsRetrospective analysis within a study evaluating post-conditioning during ST ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Indeed, experimental studies found a high accuracy and precision for contrast-enhanced SSFP based AAR estimation in vivo and ex vivo [82]. In addition, AAR quantification with contrast-enhanced SSFP imaging following STEMI has a strong correlation and low bias compared with angiographic scoring [83]. A comparison between T2-STIR and contrast-enhanced cine CMR from a DANAMI 3 sub-study revealed a higher validity for contrast-enhanced cine CMR [84].…”
Section: Myocardial Edema and Salvagementioning
confidence: 97%
“…Indeed, experimental studies found a high accuracy and precision for contrast-enhanced SSFP based AAR estimation in vivo and ex vivo [82]. In addition, AAR quantification with contrast-enhanced SSFP imaging following STEMI has a strong correlation and low bias compared with angiographic scoring [83]. A comparison between T2-STIR and contrast-enhanced cine CMR from a DANAMI 3 sub-study revealed a higher validity for contrast-enhanced cine CMR [84].…”
Section: Myocardial Edema and Salvagementioning
confidence: 97%
“…T1-and T2-weighted imaging reliably depict MaR up to one week after the myocardial infarction 101,102 . Contrast-enhanced steady state free precession imaging provides superior image quality to T2-weighted imaging and has been validated against SPECT 103 and angiographic scores 104 . Still, there has been some debate regarding the validity of CMR based evaluation of MaR 105,106 and the most appropriate timing for it, considering the bimodal pattern of edema after myocardial infarction [107][108][109][110] .…”
Section: Myocardium At Riskmentioning
confidence: 99%
“…Second, while it is known that CMR represents a widely used method of measuring the myocardial AAR during the acute phase of myocardial infarction, in our study this parameter was estimated using angiographic scoring systems. However, it should be emphasized that AAR calculated by either the BARI or the APPROACH score demonstrates a very good correlation with the respective CMR-derived values, particularly in patients presenting with STEMI [ 38 , 39 ]. In fact, estimation of MSI by combining angiographic assessment of AAR and FIS estimation by CMR has been outlined as a valid alternative [ 19 ].…”
Section: Discussionmentioning
confidence: 99%